Dissipative flow of hybrid nanomaterial with entropy optimization. (1st May 2019) - Khan, M Ijaz; Ahmad Khan, M Waleed; Hayat, T; Alsaedi, A
Abstract: Nanomaterials are a new class of materials with conceivably expansive applications in mechanical engineering processes and industry, mainly in the heat transport. Recently, a new class of nanomaterials called hybrid nanomaterials is being utilized to increase the heat transport rate. In the present communication, three-dimensional incompressible dissipative flow of hybrid nanofluid is presented by a stretchable surface of disk. Total entropy rate is calculated through implementation of second thermodynamics law. Furthermore, thermal radiation, heat source/sink and dissipation effects are considered. Convective condition for heat transfer at the boundary is implemented. The effect of pertinent parameters on the heat transfer irreversibility rate, porosity irreversibility rate, viscous dissipation irreversibility rate, Bejan number and total irreversibility rate are discussed and presented graphically. Special consideration is given to the engineering quantities like skin friction coefficient (surface drag force) and heat transfer rate (Nusselt number). From the obtained results, it is noticed that the entropy rate increases versus higher values of radiative parameter.